Analisa Pengerjaan Tirus terhadap Permukaan Benda Uji Bahan S45C Dari Variasi Putaran dan Sudut Potong Mesin Bubut Krisbow KW 15-604 - Sobar Ihsan; Budi Hartadi; Verriyanto . (Badan Kerja Sama Teknik Mesin Indonesia, 2016)
Tapered turning advantages various forms of objects with different angles of tape according to the production process. In the lathe machine, tapered turning can be done in three ways: sliding the top, headlights loose and taper attachment (taper attachment). The goal to be achieved in this study is to know the difference in the influence of variation of rotational speed Krisbow KW15-604 lathe against the smoothness of the surface of the workpiece resulting from the thinning of the material, Knowing the difference of the effect of cutting chisel angle variation to the smoothness of the surface of the workpiece resulting from the tapered turning on the material and knowing the interaction between the variation of Krisbow KW15-604 turning speed and angle cutting the chisel to the smoothness of the surface of the workpiece resulting from a tapered lathe on the material S 45C C = 47.4%, Si = 14.2%, Mn = 1.585%, Cr = 13.5%. The results of data analysis showed that there is a very significant influence between the variation of turning speed of the lathe and the variation of cutting chisel angle to the surface of the tinfoiled working object on S45C material. This can provide an overview of the metal and machinery industry in improving the quality of its products at the level of the surface in accordance with the wishes of consumers and the use of tapered products as for binding sealing on the engine of general.